2009
DOI: 10.1093/gerona/glp038
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Retinol and Other Antioxidants for Hearing Impairment Among Japanese Older Adults

Abstract: Increased serum levels of retinol and provitamin A carotenoids were clearly associated with a decreased prevalence of hearing impairment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
38
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 28 publications
3
38
0
Order By: Relevance
“…Our findings are in agreement with an animal study showing that retinoic acid (an active metabolite of retinol) prevented noise-induced hearing loss (23). These data also concur with a recent cross-sectional Japanese study of 762 adults aged 65 years or older (21). In this study, Michikawa et al showed that serum levels of retinoic acid were inversely related to the prevalence of hearing impairment.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our findings are in agreement with an animal study showing that retinoic acid (an active metabolite of retinol) prevented noise-induced hearing loss (23). These data also concur with a recent cross-sectional Japanese study of 762 adults aged 65 years or older (21). In this study, Michikawa et al showed that serum levels of retinoic acid were inversely related to the prevalence of hearing impairment.…”
Section: Discussionsupporting
confidence: 93%
“…As the concentration of vitamin A (retinol equivalents) in the inner ear has been observed to be high (21,22), the association between vitamin A and the prevention of hearing loss has been investigated. In our cohort, we observed that participants in the highest quintile of vitamin A intake compared with the remaining population were 47% less likely to have moderate or greater hearing loss (>40 dB HL).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperlipoproteinemia has been reported to cause anoxia in the sensitive cells of the inner ear and possible development of sudden fluctuating or progressive hearing and vestibular disorders related to this [15,20]. Saito et al [15] found that a high fat containing diet caused a 40% increase in the hearing threshold in their study carried out with guinea pigs.…”
Section: Discussionmentioning
confidence: 99%
“…2 Cross-sectional association of serum concentrations of retinol, provitamin A carotenoids, and other antioxidants, with hearing impairment [28]. Odds ratios (ORs) of hearing impairment were adjusted for age, sex, smoking, alcohol consumption, hypertension, and total cholesterol.…”
Section: Risk or Preventive Factors For Sensory Impairmentsmentioning
confidence: 99%